Sistem Penyaluran Zakat Mal ke Palestina di Wahdah Inspirasi Zakat Makassar Perspektif Hukum Islam - Nadila Nadila; Ahmad Syaripudin; A. Hawariah (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2023)
This study aims to determine the Zakat Mal Distribution System to Palestine in the WIZ Makassar from the Perspective of Islamic Law. The problems studied are: How is the distribution of Zakat Mal distributed to Palestine at WIZ Makassar. Is the Distribution of Zakat Mal to Palestine at WIZ Makassar in accordance with Islamic Law. This study uses an empirical juridical approach with the specification of qualitative research that is descriptive analytical. The data were obtained through interviews with several key informants and were supported by legal materials obtained from literature. The research results are as follows; first, an illustration of the distribution of zakat mal to Palestine by WIZ is by first collecting zakat funds from the muzakki then WIZ Makassar cooperates with the NGO, DPP Wahdah Islamiyah as supervisor of the distribution program and independent financial audit. Second, in terms of distributing zakat to other countries such as Palestine, Islamic scholars argue that it is permissible with the following details. The Syafii Mazhab allows zakat funds to be distributed if there are no mustahik in the area where the zakat is collected, the Hanafi Mazhab says it is permissible to distribute zakat to other areas if there are relatives who are more in need or channeled to the claimants of knowledge. The Hambali and Maliki Mazhab are of the opinion that it is permissible to distribute zakat to an area close to the place where zakat is obligatory, which is less than the distance of the qasar prayer.